STRENGTHENING AND MANAGEMENT OF CAMPUS-BASED INDONESIAN LANGUAGE INSTITUTIONS FOR FOREIGN SPEAKERS (BIPA) IN INDONESIAN LANGUAGE AND LITERATURE EDUCATION PRODUCTS AL WASHLIYAH NUSANTARA MUSLIM UNIVERSITY WITH THE LANGUAGE CENTER OF NORTH SUMATRA PROVINCE - Abdullah Hasibuan; Nirmawan; Tiflatul Husna (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Indonesian is experiencing very rapid development in various corners of the world. This is also influenced by various factors, including Indonesia's state relations with other countries in various sectors, both economic, political, social and cultural. Through this relationship, the important role of Indonesian is believed to be an element that has the potential to be related to the position of Indonesian on the international stage (Muliastuti, 2016). Apart from that, in accordance with the mandate of Law Number 24 of 2009 concerning the Flag, Language and National Emblem, namely making Indonesian an international language, gradually and systematically, under the Ministry of Education and Culture, various diplomatic methods are carried out. One of the missions The linguistic diplomacy that is intensively carried out by the Indonesian government is by facilitating the Indonesian language teaching program for Foreign Speakers (BIPA) to many countries that already have bilateral and multilateral cooperation with Indonesia. Through language, someone can communicate with other people, even though they have different cultural backgrounds. Likewise with Indonesian which is learned by people who are not native speakers of the language. Therefore, the BIPA teaching program, which is one of the advantages of this diplomatic mission, continues to be intensified at various universities, agencies or language institutions abroad.